2016
DOI: 10.15416/pcpr.2016.1.3.76
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Side Effects of Deferasirox and Deferiprone for Thalasemia Major in Children

Abstract: Thalassemia major (TM) is an inherited disease caused by defective or absent of hemoglobin chain synthesis. Regular chelation therapy is necessary to reduce excess iron in several organs of TM patients. The most commonly used chelating agents are deferasirox and deferiprone. However, information regarding their effectiveness and side effects in Indonesian children population with TM were limited. This study was conducted to assess the effectiveness and side effects of deferasirox and deferiprone in pediatric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A study indicated that the best drug for the treatment of transfusion iron overload is DFO, especially when used continuously instead of intermittently [ 34 ]. Another study suggests that DFO was more effective than DFP in the treatment of TM and reduction of the ferritin level [ 41 ]. In β -thalassemic patients, iron chelation with DFO has reduced and deferred liver disease, diabetes, endocrine failure, and normalized growth and prevented cardiac insufficiency [ 42 ].…”
Section: Different Types Of Iron Chelatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study indicated that the best drug for the treatment of transfusion iron overload is DFO, especially when used continuously instead of intermittently [ 34 ]. Another study suggests that DFO was more effective than DFP in the treatment of TM and reduction of the ferritin level [ 41 ]. In β -thalassemic patients, iron chelation with DFO has reduced and deferred liver disease, diabetes, endocrine failure, and normalized growth and prevented cardiac insufficiency [ 42 ].…”
Section: Different Types Of Iron Chelatorsmentioning
confidence: 99%
“…The results for the most efficient iron chelator in reducing myocardial iron and hepatic iron were DFP and DFO, respectively [ 65 ]. The DFP is used in the treatment of blood disorders, such as thalassemia, and its effectiveness was assessed in some studies [ 41 ] ( Table 2 ).…”
Section: Different Types Of Iron Chelatorsmentioning
confidence: 99%